New Formulation for Organic Mineral Nutrition of Plums to Achieve Higher Yield and Better Chemical Composition of Leaves and Fruits - Marina T. Stojanova; Dragutin A. Djukic; Monika Stojanova; Aziz Şatana (Applied Fruit Science, Springer, 2024)
The impact of foliar fertilization on the yield and chemical composition of the ‘Stenlej’ plum cultivar grown in North Macedonia was studied with multiple experimental variants as follows: 1. Control (untreated); 2. NPK+Ever green with Me (55% organic matter, 2% w/w Mg, 2% w/w Fe, 2% w/w Zn, 2% w/w Mn, 0.5% w/w Cu, 0.5% w/w B); 3. NPK+Biolinfa (34% organic matter 3% N, 5.80% K2O); 4. NPK+Oligomix (1.20% B, 0.10% Cu, 4% Fe, 1.50% Mn, 0.10% Mo, 2% Zn). Before setting up the experiment, soil agrochemical analyses were performed, and it was concluded that fertility was good in terms of nitrogen but medium in terms of phosphorus and potassium. Foliar fertilizing has a positive influence on the yield and chemical composition of leaves and plum fruits. The highest (p < 0.05) average plum fruit yield (18,255 kg∙ha−1) was determined in variant 2. The same variant was characterized by the highest (p < 0.05) average content of nitrogen (3.10%), phosphorus (0.35%) and potassium (2.15%) in plum leaves and plum fruits (3.40% N, 1.35% P2O5, 3.87% K2O).